Magmatic PGE sulphide mineralization in clinopyroxenite from the platreef, bushveld complex, South Africa - Klemd, Reiner; Beinlich, Andreas; Kern, Matti; Junge, Malte; Martin, Laure; Regelous, Marcel; Schouwstra, Robert (Minerals, 2020)
The Platreef, at the base of the northern limb of the Bushveld Complex in South Africa, hosts platinum-group element (PGE) mineralization in association with base-metal sulphides (BMS) and platinum-group minerals (PGM). However, whilst a magmatic origin of the stratiform mineralization of the upper Platreef has been widely confirmed, the processes responsible for the PGE and BMS mineralization and metasomatism of the host rocks in the Platreef are still under discussion. In order to contribute to the present discussion, we present an integrated petrographical, mineral-chemical, whole-rock trace-and major-element, sulphur-and neodymium-isotope, study of Platreef footwall clinopyroxenite drill core samples from Overysel, which is located in the northern sector of the northern Bushveld limb. A metasomatic transformation of magmatic pyroxenite units to non-magmatic clinopyroxenite is in accordance with the petrography and whole-rock chemical analysis. The whole-rock data display lower SiO2, FeO, Na2O and Cr (<1700 ppm), and higher CaO, concentrations in the here-studied footwall Platreef clinopyroxenite samples than primary magmatic Platreef pyroxenite and norite. The presence of capped globular sulphides in some samples, which display differentiation into pyrrhotite and pentlandite in the lower, and chalcopyrite in the upper part, is attributed to the fractional crystallization of a sulphide liquid, and a downward transport of the blebs. In situ sulphur (V-CDT) isotope BMS data show isotopic signatures (δ34S = 0.9 to 3.1 ‰; ∆33S = 0.09 to 0.32‰) close to or within the pristine magmatic range. Elevated (non-zero) ∆33S values are common for Bushveld magmas, indicating contamination by older, presumably crustal sulphur in an early stage chamber, whereas magmatic δ34S values suggest the absence of local crustal contamination during emplacement. This is in accordance with the εNd (2.06 Ga) (chondritic uniform reservoir (CHUR)) values, of −6.16 to −6.94, which are similar to those of the magmatic pyroxenite and norite of the Main Zone and the Platreef in the northern sector of the northern Bushveld limb. Base-metal sulphide textures and S–Se-ratios give evidence for a secondary S-loss during late-to post-magmatic hydrothermal alteration. The textural evidence, as well as the bulk S/Se ratios and sulphide S isotopes studies, suggest that the mineralization in both the less and the pervasively hydrothermally altered clinopyroxenite samples of Overysel are of magmatic origin. This is further supported by the PPGE (Rh, Pt, Pd) concentrations in the BMS and mass-balance calculations, in both of which large proportions of the whole-rock Pd and Rh are hosted by pentlandite, whereas Pt and the IPGE (Os, Ir, Ru) were interpreted to mainly occur in discrete PGM. However, the presence of pentlandite with variable PGE concentrations on the thin section scale may be related to variations in the S content, already at S-saturation during magmatic formation, and/or post-solidification mobilization and redistribution.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Bushveld Complex; Clinopyroxenite; Fluid–rock interaction; Metasomatism; Platreef

Permian age of orogenic thickening and crustal melting in the Garm Block, South Tien Shan, Tajikistan - Konopelko, Dmitry; Klemd, Reiner; Mamadjanov, Y.; Hegner, E.; Knorsch, Manuel; Fidaev, D.; Kern, Matti; Sergeev, S. (Journal of Asian Earth Sciences, 2015)
In this paper we present new data for the metamorphic Garm Block (150 × 40 km) that was traditionally shown on regional maps as fragment of a Precambrian basement. The Garm Block comprises migmatized gneisses and schists for some of which peak metamorphic conditions (600–660 °C at 7–9 kbar) characteristic for medium P/T series metamorphic belts were determined. U–Pb ages of overgrown rims of zircon grains and newly grown magmatic zircon grains from four migmatitic samples indicate that melting occurred during peak metamorphic conditions between 299 and 290 Ma. Thus the Garm Block is the first Early Permian regional metamorphic terrane established in the southern part of the Central Asian Orogenic Belt. A crosscutting granite intrusion yields a concordia age of 290 Ma identical to the age of metamorphism and similar to ages of post-collisional intrusions elsewhere in the Tien Shan. Detrital zircon grains from the Garm samples yield an age spectrum with major peaks at 700–550 Ma and 1150–700 Ma, and smaller ones at ca. 2.7–2.4 Ga and 3.5–3.3 Ga. The youngest grains define an Ediacarian maximum depositional age of the sedimentary protoliths. The presence of Grenvillian ages of 1150–800 Ma, which are characteristic for the Tarim Craton, and the lack of ca. 1.6–1.2 Ga ages, characteristic for the Northern Tien Shan, suggest an origin of the Precambrian zircon grains from southern continental blocks similar to the Tarim Craton. Six granitoid samples yield negative εNd values of −10.6 to −3.7 consistent with the reworking of crustal material with 1.8–1.1 Ga average crustal residence times and the formation of the South Tien Shan belt on a continental basement with Paleoproterozoic or older crust. The Garm Block formed as a consequence of lithospheric thickening during the Late Carboniferous collision of two continental blocks that created the South Tien Shan fold belt. Lateral crustal melt flow coupled with extension may have resulted in exhumation of the Permian metamorphic rocks.<br
Keywords: Tajikistan; South Tien Shan (Tianshan); Garm Block; Permian metamorphism; Zircon ages; Nd isotopes